Design of Low altitude Flight Data Security Sharing Platform Based on Blockchain Technology - Yu, Jiayin; Wei, Lina; Gong, Quanwei; Zhou, Jingchao; Zhang, Xinyue (Procedia computer science, 2025)
At present, low-altitude flight data sharing faces problems such as insufficient data security, high risk of data tampering, and imperfect access control. To solve these problems, this study designs and implements a low-altitude flight data security sharing platform based on blockchain technology. First, Hyperledger Fabric is used to build a blockchain architecture to ensure the immutability and traceability of data. Secondly, Solidity is used to write smart contracts to achieve fine-grained data access control and permission management. Finally, the AES-256 encryption algorithm is integrated to encrypt the data transmission process to improve the security of overall data transmission. In the experimental conclusion, the research platform can effectively detect and prevent malicious tampering in terms of data tampering protection. For example, in the data tampering experiment, the tampered hash value is inconsistent with the original hash value, and the tampering behavior is successfully identified. In terms of access control efficiency, the average response time of the administrator is about 0.2 seconds. In the system stability evaluation, when the platform processes 500 concurrent requests, the average response time is 1.5 seconds, the CPU utilization rate reaches 85%, and the memory consumption is 500MB. In the above data conclusions, the feasibility and superiority of the blockchain-based low-altitude flight data security sharing platform in practical applications are demonstrated.